Bank-related loan supply factors during the crisis: An analysis based on the German bank lending survey - Barno Blaes (Deutsche Bundesbank, 2011)
This paper analyses the role of bank-related constraints in explaining the sharp slowdown in bank lending to non-financial corporations in Germany during the recent financial crisis. We use a panel approach based on a unique data set which matches the individual responses of the banks participating in the Eurosystem's Bank Lending Survey with the corresponding micro data on loan quantities and prices. Our main finding is that bank-related supply and demand-side indicators were both important in explaining the slowdown of bank lending during the crisis years. The results suggest that the dampening impact of the bank-related restrictions was strongest from the third quarter of 2009 to the first quarter of 2010. Over this short period, more than one-third of the explained negative loan development was due to the restrictive adjustments of purely bank-related factors, such as the costs related to the bank's capital, market financing conditions and the bank's liquidity position.
Keywords: C23; E30; E51; G21; 330; Bank Lending Survey; credit supply; panel data; financial crisis; Germany; Kreditgeschäft; Finanzmarktkrise; Kreditrationierung; Schätzung; Deutschland